2021
DOI: 10.29309/tpmj/2021.28.06.6258
|View full text |Cite
|
Sign up to set email alerts
|

To determine the correlation between mean platelet count and frequency of grading of esophageal varices in patients of liver cirrhosis.

Abstract: Objectives: To determine the correlation between mean platelet count and grading of esophageal varices in patients of liver cirrhosis. Study Design: Cross Sectional study. Settings: Department of Medicine, DHQ Hospital (FMU) &AFM&DC Faisalabad. Period: 17th August 2019 to 16th February 2020. Material & Methods: A total of 105 patients liver cirrhosis with esophageal varices were included in the study according to the inclusion and exclusion criteria. For assessment of platelet count 2ml blood sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Literature review revealed that in the severe state of liver cirrhosis there is hemostatic disturbance specifically thrombocytopenia has been noted in which platelet count is less than 150,000/ul so testing platelet count can be a predictor of liver cirrhosis developed complications like esophageal varices (17). Literature review revealed that there is a strong association between the low platelet count and development of esophageal varices (18). Current study also found a strong significant association between the platelet count and presence of esophageal varices.…”
Section: Discussionsupporting
confidence: 64%
“…Literature review revealed that in the severe state of liver cirrhosis there is hemostatic disturbance specifically thrombocytopenia has been noted in which platelet count is less than 150,000/ul so testing platelet count can be a predictor of liver cirrhosis developed complications like esophageal varices (17). Literature review revealed that there is a strong association between the low platelet count and development of esophageal varices (18). Current study also found a strong significant association between the platelet count and presence of esophageal varices.…”
Section: Discussionsupporting
confidence: 64%
“…This meta-analysis included eight articles comprising 1008 patients. Among these studies, one study was conducted in China [12], two studies were conducted in Egypt [20], [21], one study was conducted in India [26], three studies were conducted in Pakistan [10], [19], [27], [28], and one study was conducted in Singapore [28]. Three studies were prospective observational [12], [20], [21] and five were cross-sectional [10], [19], [27], [28], [29].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…From eight studies consisting of 1008 patients, seven studies reported a negative correlation between platelet count and grading of esophageal varices in liver cirrhosis patients [12], [19], [20], [21], [27], [28], [29], while one study reported a positive correlation coefficient [10]. A meta-analysis was done on eight eligible studies, the result of the forest plot showed that there is a significant moderate negative correlation between platelet count and grading of esophageal varices in liver cirrhosis patients, with a pooled correlation coefficient (r) of -0.42 (95%CI -0.65 to -0.13; p = 0.005) (Figure 2).…”
Section: Platelet Count and Grading Of Esophageal Varicesmentioning
confidence: 99%
See 2 more Smart Citations